PENGARUH PERSEPSI KONSUMEN ATAS BRAND EXTENSION DAN INTENSITAS ELECTRONIC WORD OF MOUTH TERHADAP BRAND IMAGE LOFFLE POP UP DESSERT - Puspita Mei Wardani; Djoko Setyabudi (Interaksi Online, 2018)
Brand image becomes very important for certain brand so it can stay last in the middle of the business competitio. But on the reality, Loffle’s ranking on TripAdvisor has declined over the past few months. This indicates that Loffle’s position is not strong enough in the minds of Semarang citizen. Recently Loffle applied brand extension strategy through Koka Cheese Tea. This is the reason underlying the authors to examine whether consumer perceptions of brand extensions and electronic word of mouth intensity influence Loffle's image. This study aims to determine the effect of consumer perceptions of brand extension and electronic word of mouth intensity upon Loffle's brand image with a sample of 80 people who had consumed Koka Cheese Tea and lived in Semarang. The technique used in collecting primary data is purposive sampling using data collection tools and techniques in the form of questionnaires and short interviews to enrich the information obtained. Based on the results of data processing using the SPSS 20.0 application through a simple linear regression test shows that the significance value for the consumer perception variable on brand extension is 0,000, which means that there is a significant influence. It shows that consumer perceptions of brand extension (X1) affects Loffle's brand image (Y), and it is 18.6 percent. On testing the electronic word of mouth intensity variable obtained a significance value of 0.029 which means significant. It shows that electronic word of mouth intensity (X2) affects Loffle's brand image (Y) and there is an exact influence of 6 percent. The conclusion of this study is the variable influence of consumer perception on brand extension and the intensity of electronic word of mouth affect the Loffle Pop Up Dessert’s brand image. Researcher's suggestion for further research is to retest another factors of brand image builder. Researcher also suggested that Loffle create e-wom by involving customers as information dissemination agents.